Social Justice and Humanity on Polygamous Marriage at the Religious Court of Pasuruan, Indonesia - Mukhammad Nur Hadi; Faridatus Suhadak; Zuliza Mohd Kusrin (Justicia Islamica, 2023)
Polygamy can be granted if it meets one of the alternative conditions and the absolute cumulative condition. However, sometimes alternative terms are used as wrappers for other reasons to look ridiculous, such as humanity. This paper examines three polygamy rulings at the Pasuruan Religious Court in 2019 using the three Indonesia Women Ulama Congress (KUPI) fatwa approaches ma’ruf, mubadalah, and ultimate justice. The article finds that the reason for public justice is used to wrap up humanitarian reasons. In the ma’ruf approach, the standard of public justice as the basis for judges' consideration needs to be more precise because it does not refer to the global public experience. These standards are not in harmony with the decent logic of women in general. The Mubadalah approach ensures a balanced interpretation and interplay of public justice and humanity. The judge’s reasoning for considering standards of public justice and humanity based on patriarchal paradigms deserves to be criticized. The ultimate justice approach illustrates that the judge's reasoning is not based on women's biological, sociological, and anthropological life experiences in the case of polygamy. Using justice and justifying humanitarian reasons in some polygamy rulings in the Pasuruan Religious Court does not yet have a solid basic legal paradigm